Legalization of the linguistic intelligence scale of (Gardner) on a sample of Kurdish children (a suggested family counseling program to address linguistic interference) (Journal of the College of Basic Education, 2022)
The current research aims to apply and standardize Gardner’s linguistic intelligence scale after its Arabization and standardization on the Kurdish environment and its application with the aim of measuring and identifying the level of linguistic intelligence on the Arabic and Kurdish scales at the same rate according to the variable of the population. Gender (male - female), and for the purpose of achieving the research objectives, the researcher adopted the scale (Gardner), the pioneer of the theory of multiple intelligences adopted in the current research in its Arabic version and translated into the Kurdish language, and after calculating it by checking the characteristics of the psychometric measurements. On a sample of (30) children (13) males and (17) females, and after data collection and statistical analysis, it appeared that the sample members have linguistic intelligence on the Kurdish-based environment-scaled environment-based scale. Comparing them with the second value of the calculated logger and the hypothetical mean of (5.5), the study also concluded that there were no significant differences Statistical significance in accordance with the variable of the type (male and female), and the study came out with a number of recommendations and proposals, which are: - Building guiding programs to improve and develop linguistic intelligence for the children of the individuals to help them to mastery of their mother tongue as the researcher recommended to conduct studies that are compared to To verify the following hypothesis: -The mother tongue hinders the mastery of other languages, and the reason may be the overlap between languages that negatively affects the linguistic intelligence of children and causes cognitive distortions, and this is the main motive of the study that the study sought to verify. It will not be beyond the ages.